CONTENT VALIDITY RATIO AND CONFIRMATORY FACTOR ANALYSIS OF THREE TIER TEST INSTRUMENT ON SOLUTION BALANCE CONCEPTS - Tuherni, Erni; Nursa'adah, Euis; Affifah, Isriyanti (Jurnal Pengajaran MIPA, 2020)
Three tier test is one of the instruments which can be used to detect conception level of the students. This developed-three tier test instrument consists of three levels of question. The first tier is multiple choice, the second tier is reason to choose the answer, and the third tier is affirmative question about the belief of the answers chosen on the first and second tier. An instrument can be used as it well-qualified; that can be seen from its validity and reliability value.  One of the methods that used to measure the instrument’s validity is Content Validity Ratio (CVR) and Confirmatory Factor Analysis (CFA) while a method that used to measure the instrument’s reliability is cronbach test.  The quality of tree tier instrument test, based on CVR result in an average 0.64, indicates that the instrument had owned conformity content with the measured-domain, and CFA in a MSA-average 0.805, indicates that the instrument had been valid and can develop the construct that measured in accordance with the developed-indicators as well as the three tier instrument’s reliability in Cronbach’s Alpha value 0.927 insists that the three tier instrument that developed has a quite good reliability value. Among 27 instruments that had been analyzed, 12 instruments of them considered valid based on CVR and CFA examination result.  ABSTRAK Three tier adalah salah satu instrumen yang dapat digunakan dalam mendeteksi tingkat konsepsi yang terjadi pada peserta didik. Instrument Three Tier yang dikembangkan ini meliputi 3 tingkatan soal. Pada tingkat pertama (First-tier) berupa pilihan ganda, tingkat kedua (Second-tier) berupa alasan dalam pemilihan jawaban, dan tingkat ketiga (Third-tier) berupa pertanyaan penegasan tentang keyakinan dari jawaban yang telah dipilih pada tingkat satu dan dua. Suatu instrumen dapat digunakan apabila memiliki kualitas yang baik dilihat dari nilai validitas dan reliabilitas. Salah satu metode yang digunakan untuk mengukur validitas instrumen yaitu dengan menggunakan content validity ratio (CVR) dan confirmatory factor analysis (CFA). Kualitas instrument three tier berdasarkan hasil CVR (Content Validity Ratio) dengan rata-rata nilai 0,64 menunjukkan instrumen telah memiliki kesesuaian isi dengan domain yang diukur, dan CFA (Confirmatory Factor Analysis) dengan nilai MSA rata-rata sebesar 0,805 menunjukkan bahwa instrumen telah valid dan dapat membangun konstruk yang diukur sesuai dengan indikator yang dikembangkan serta realiabilitas instrument three tier dengan nilai Cronbach’s Alpha sebesar 0,927 mengungkapkan bahwa instrument three tier yang dikembangkan memiliki nilai reliabilitas yang cukup baik. Dari 27 instrumen yang dianalisis, terdapat 12 instrument three tier yang valid berdasarkan hasil uji CVR dan CFA.